Determinants of Nurses’ Work Motivation in the Implementation of Nursing Care at the Cilincing Regional General Hospital, North Jakarta, in 2025 - Yanuar Jak; Eka Yoshida; Marco Judika Hutagaol (CV. AFDIFAL MAJU BERKAH, 2026)
Nurses' work motivation is an important factor in the implementation of nursing care. High work motivation will help improve nurses' performance so they can provide quality health services. This study aims to determine the determinants of nurses' work motivation in the implementation of nursing care at Cilincing Regional General Hospital, North Jakarta in 2025. The research method used is quantitative analytic with a cross-sectional design. The number of samples was 54 nurses. Data collection used a questionnaire. Data analysis used univariate, bivariate (Chi-square test) and multivariate (logistic regression). The results of the study showed that most employees had high work motivation (59.3%). The results of the bivariate analysis, variables that had a significant relationship with nurses' work motivation were Rewards (p = 0.002 and OR = 7.583), training (p = 0.013 and OR = 5.159), supervision (p = 0.026 and OR = 6.842), perception of rewards/salary (p = 0.001 and OR = 9.450), coworker relationships (p = 0.007 and OR = 7.000), and work environment (p = 0.0001 and OR = 18.000). The results of the multivariate analysis, it turned out that the most dominant factor was the work environment variable (p = 0.002 and OR = 33.196). This study concluded that the work environment had the highest influence on nurses' work motivation.It is recommended to maintain and preserve a conducive working environment for nurses in order to support their performance and well-being. Additionally, the frequency of supervision should be increased, both by the head nurses and the department heads, to ensure the quality of nursing care and adherence to established standards. The use of an objective and measurable application system, such as the e-Employee system, is also suggested to facilitate fair compensation and streamline the process of training applications